ANALISIS RISIKO ERGONOMI DAN KELUHAN GANGGUAN MUSKULOSKELETAL PADA PEKERJA BONGKAR MUAT (Program Studi Ilmu Kesehatan STIKESÂ Abdi Nusa Pangkalpinang, 2021)
Musculoskeletal disorders (MSDs) are a group of symptoms / disorders related to muscle tissue, tendons, ligaments, cartilage, nervous system, bone structure and blood vessels. Musculoskeletal complaints that workers feel in the skeletal muscle range from minor complaints to very painful complaints. This study aims to analyze the description of ergonomic risks and complaints of musculoskeletal diseases in workers at PT. Bhanda Graha Reksa Palembang. This type of research uses a cross sectional study design. The population of this study were all workers in the loading and unloading sector who worked at PT. Bhanda Graha Reksa Palembang branch which stated 115 people. Sampling using random sampling technique. Data collection using the method of observation and questionnaires. Data analysis used bivariate analysis with Chi Square test (Î± = 0.05), and multiple logistic regression tests for multivariate analysis. The results showed that 77.8% of workers experienced severe MSDs complaints. The results of the bivariate analysis showed MSDs complaints with ergonomic risk (p value = 0.009), age (p value = 0.002), years of service (p value = 0.000), and exercise habits (p value = 0.017). While the smoking habit variable (p value = 0.228), and body mass index (p value = 0.399). It can be ignored that the variables age, habits and ergonomic risk are variables that influence MSD complaints and the most dominant variable is age. Workers either take breaks or stretch when they begin to feel stress on the muscles of the body. Seeing the great benefits, you should regularly do morning exercises. Although in this study smoking had no effect, it was a suggestion for workers to stop smoking.